Folk ornament in Soviet documentary films of Kazakhstan and Kyrgyzstan: stages of fixation and comprehension historical memory - Manichkin, Nestor A. (The New Research of Tuva, 2024)
The article is dedicated to the representations of folk ornamentation and traditional crafts of Kazakhs and Kyrgyz people in documentary films made during the Soviet era in Kazakhstan and Kyrgyzstan. In conjunction with ornament, such popular sources often explore associated, symbolically charged forms of visual culture of these peoples: petroglyphs, tamgas, ancient scripts, etc. Considering cinema as one of the types of historical discourse, the author is looking for evidence of memory politics in it. The article analyzes fifteen documentary films created during the period of 1936–1984, from reports in newsreels to full-length films. The studied films are archived in the Central State Archive of Film, Photo, and Sound Records of the Republic of Kazakhstan and the Central State Archive of Film, Photo, and Sound Records of the Kyrgyz Republic. Examining and interpreting the film materials allows for identifying certain features of cultural politics related to questions of historical memory and ethno-cultural identification. The author examined the development of documentary cinematography dedicated to ornamentation in the context of the adaptation and modernization of traditional crafts in Central Asia, the evolution of academic representations of traditional signs and symbols of Kazakhs and Kyrgyz people, and the activities of the Soviet intelligentsia. The analysis demonstrates how narratives, images, and artistic features displayed on screen have changed: if before the 1970s there was a prevailing rigid ideological line, including the appropriation of ornament, and its connection with historical memory was either ignored or interpreted strictly in a class-based and socialist realist reading (with authors being documentarians and reporters from Moscow and Leningrad), then in subsequent films about the ornament and folk art of Kazakhs and Kyrgyz people, themes of nomadism, unity of nature and man, ancestral heritage, characteristic of ethno-metaphysics and essential for the creation of national identity, began to appear more frequently (with authors being directors, screenwriters, and artists from Kazakhstan and Kyrgyzstan). This was particularly evident in those documentary films that employed poetic cinema techniques.